Master Students’ Readiness In Taking English Proficiency Test During The Pandemic Time - Setya Putri Rahayu (Lembaga Pengembangan Kinerja Dosen, 2022)
English Proficiency Test becomes a compulsory standard for higher education settings. Students need to perform their best capability, so they can obtain their expected score. Meanwhile, way of learning changed significantly due to Covid-19 pandemic. Students had to adjust the shifting way of learning from face-to-face meeting to online learning. The study aimed to investigate master students’ readiness in taking English Proficiency Test during the pandemic due to shifting way of learning from face-to-face to online learning. The research employed mixed-method study by using phenomenology approach as the qualitative inquiry, and descriptive analysis was used as the quantitative investigation. Qualitative data were taken through interview, and quantitive data were obtained by using questionairre. Based on the results of the study, it can be known that respondents did not perform their good self-efficacy in doing their English Proficiency Test. Meanwhile, respondents needed to adjust the shifting of learning way during pandemic because they should be more independent by learning the materials individually.